2013
DOI: 10.1007/s00792-013-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical properties of an extreme ‘salt-loving’ proteasome activating nucleotidase from the archaeon Haloferax volcanii

Abstract: In eukaryotes, the 26S proteasome degrades ubiquitinylated proteins in an ATP-dependent manner. Archaea mediate a form of post-translational modification of proteins termed sampylation that resembles ubiquitinylation. Sampylation was identified in Haloferax volcanii, a moderate halophilic archaeon that synthesizes homologs of 26S proteasome subunits including 20S core particles and regulatory particle triple-A ATPases (Rpt)-like proteasome-associated nucleotidases (PAN-A/1 and PAN-B/1). To determine whether sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These prior studies indicate that CC domains are allosterically linked to the ATPase domains, yet no studies have shown how the CCs function mechanistically to regulate protein degradation by the proteasome. Much like the 19S ATPases, some studies suggest that the CC domains from PAN are also involved in substrate binding, although it is thought that PAN can achieve this without using additional substrate receptors that are found in the 19S 30 , 31 , 33 36 .…”
Section: Introductionmentioning
confidence: 99%
“…These prior studies indicate that CC domains are allosterically linked to the ATPase domains, yet no studies have shown how the CCs function mechanistically to regulate protein degradation by the proteasome. Much like the 19S ATPases, some studies suggest that the CC domains from PAN are also involved in substrate binding, although it is thought that PAN can achieve this without using additional substrate receptors that are found in the 19S 30 , 31 , 33 36 .…”
Section: Introductionmentioning
confidence: 99%
“…There is little information about the proteasome concerning halophilic archaea; but the proteasome system in Hfx. volcanii has been widely studied in the presence of some stressors (high temperature, low salt, and the addition of l -canavanine), making it the best studied organism in haloarchaea [ 126 , 127 ]. This research concludes that psmA and panA are required to withstand low salt stress and l -canavanine, while psmA helps to overcome the hypersensitive responses of high temperature stress.…”
Section: Response To Stress In Halophilic Archaeamentioning
confidence: 99%
“…Thus, the PANs may form weak associations with the SAMPs alone. Far Western experiments demonstrate that the full-length PAN-A/1 binds the sampylation target MoaE only when covalently linked to SAMP1 (101). Thus, at least PAN-A/1 appears to have a higher affinity for SAMP1 when covalently bound to a target protein compared with SAMP1 alone, suggesting sampylation triggers association of protein targets with the proteasomal ATPase.…”
Section: Prokaryotic Forms Of Ubiquitylationmentioning
confidence: 99%